2018
DOI: 10.1016/j.anifeedsci.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary nitrate on enteric methane emissions, production performance and rumen fermentation of dairy cows grazing kikuyu-dominant pasture during summer

Abstract: Highlights• Dietary nitrate as methane mitigation strategy for grazing dairy cows • Concentrate DMI and milk yield decreased with nitrate addition • Total DMI was unaffected by treatment • Methane production and yield tended to decrease with nitrate addition • Ruminal pH fluid and total VFA concentration increased with nitrate addition AbstractDietary nitrate supplementation is an effective methane (CH4) mitigation strategy in total mixed ration based diets fed to ruminants. To date, limited information is ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 42 publications
0
16
0
2
Order By: Relevance
“…Multiparous Jersey cows (average bw 408 kg) were acclimated for 3 weeks to increased dietary nitrate levels (n = 20), followed by 8 weeks on 0, 11 and 23 g of NO 3 -/kg (DM) corresponding approximately to 0, 150 or 310 mg NO 3 -/kg bw per day, given in concentrate feed (DMI of concentrate 5.4 kg/day). Cows exposed to 314 mg NO 3 -/kg bw per day showed 12% lower milk yield and 13% lower fat milk than the control with no effects observed in the 150 mg/kg bw per day group for milk protein (van Wyngaard et al, 2018). Reduced protein content of milk by 9% was also observed in Jersey cows (default bw average 454 kgsee NRC, 2001) fed diet containing 15 g NO 3 -/kg feed DM (corresponding approximately to 570 mg/kg bw per day with a DMI of 17.2 kg DMI), compared with controls (Meller et al, 2019).…”
Section: Lactating Cowsmentioning
confidence: 81%
“…Multiparous Jersey cows (average bw 408 kg) were acclimated for 3 weeks to increased dietary nitrate levels (n = 20), followed by 8 weeks on 0, 11 and 23 g of NO 3 -/kg (DM) corresponding approximately to 0, 150 or 310 mg NO 3 -/kg bw per day, given in concentrate feed (DMI of concentrate 5.4 kg/day). Cows exposed to 314 mg NO 3 -/kg bw per day showed 12% lower milk yield and 13% lower fat milk than the control with no effects observed in the 150 mg/kg bw per day group for milk protein (van Wyngaard et al, 2018). Reduced protein content of milk by 9% was also observed in Jersey cows (default bw average 454 kgsee NRC, 2001) fed diet containing 15 g NO 3 -/kg feed DM (corresponding approximately to 570 mg/kg bw per day with a DMI of 17.2 kg DMI), compared with controls (Meller et al, 2019).…”
Section: Lactating Cowsmentioning
confidence: 81%
“…A feeding trial in South Africa using the SF 6 tracer technique found that increasing dietary feed concentrate levels to a basal diet of pasture for exotic purebred (Jersey) cows reduced CH 4 yield by ~14% from the lowest (29.1 g CH 4 kg -1 DMI) to highest concentrate feeding level (25.1 g CH 4 kg -1 DMI) (59). Another study in South Africa found that increasing dietary nitrate levels decreased CH 4 emissions from Jersey cows on seeded pasture diets, with CH 4 yield declining from 21.8 g CH 4 kg -1 DMI in the control diet to 20.1 g CH 4 kg -1 DMI (-8%) for low and 18.7 g CH 4 kg -1 DMI (-14%) for high nitrate feeding levels (60).…”
Section: Practices To Reduce Enteric Ch 4 Emissionsmentioning
confidence: 96%
“…Perbedaan suhu lingkungan dapat berdampak pada produksi gas metana di manur ternak, yakni secara umum produksi metana dari manure akan meningkat dengan semakin meningkatnya suhu lingkungan (IPCC 2006). Saat musim panas, emisi gas metana enterik pada sapi Jersey di awal laktasi yang digembalakan dan diberi pakan tambahan konsentrat adalah sebesar 280-313 g/ekor/hari (van Wyngaard et al 2018a). Sedangkan saat musim semi sebesar 400-405 g/ekor/hari (van Wyngaard et al 2019).…”
Section: Produksi Gas Metana Enterik Dan Faktor-faktor Yang Mempengaruhinyaunclassified